1992
DOI: 10.1093/jnci/84.5.328
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Therapy With Low-Dose Isotretinoin for Prevention of Basal Cell Carcinoma: A Multicenter Clinical Trial

Abstract: The toxicity associated with the long-term administration of isotretinoin, even at the low dose used in this trial, must be weighted in planning future prevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 0 publications
3
68
0
3
Order By: Relevance
“…125 Oral retinoids (acitretin, oral retinol, and isotretinoin) also do not appear to reduce the incidence of BCC in those with a history of a keratinocyte cancer. [126][127][128][129] Limited evidence is available to support the utility of other agents, including oral nicotinamide, a-difluoromethylornithine, and celecoxib, in reducing the risk for keratinocyte cancer in patients with history of BCC. There is early evidence from a small trial that oral nicotinamide may reduce the risk for subsequent keratinocyte carcinoma in nonimmunosuppressed individuals with a history of such Table XIII.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…125 Oral retinoids (acitretin, oral retinol, and isotretinoin) also do not appear to reduce the incidence of BCC in those with a history of a keratinocyte cancer. [126][127][128][129] Limited evidence is available to support the utility of other agents, including oral nicotinamide, a-difluoromethylornithine, and celecoxib, in reducing the risk for keratinocyte cancer in patients with history of BCC. There is early evidence from a small trial that oral nicotinamide may reduce the risk for subsequent keratinocyte carcinoma in nonimmunosuppressed individuals with a history of such Table XIII.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
“…[116][117][118][119]123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] …”
Section: Follow-up and Reducing Risk For Future Skin Cancersunclassified
“…Retinoids other than retinol have been most commonly used in human chemoprevention trials (2,3,5,6). A disadvantage of one of the most commonly tested synthetic retinoids, isotretinoin, is that it causes adverse effects such as increases in triacylglycerol concentrations and skeletal changes even at relatively low doses (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Also, long-term therapy with low doses of systemic retinoids such as isotretinoin/ATRA and 13-cis retinoic acid, was not effective in reducing the occurrence of BCCs at new sites in patients with previously reported small numbers (1, 2) of BCCs (31). The differences between our observations and those observed for skin cancer patients treated with systemic retinoids may be (a) mode of delivery: topical tazarotene application may result in more retinoid reaching the tumor cells; (b) type of retinoid: the human studies were carried out using other pan-RAR agonists (that is, 13-cis retinoic acid and ATRA); from our observations, the outcome of activating different RARs in the skin may be quite different; (c) there may be a species difference in the response to retinoids; and/or (d) the sustained and curative effects of tazarotene applied topically may be specific to microscopic BCCs; previous observations showed that systemic retinoids prevented the occurrence of new BCCs in BCNS patients during therapy but had no effect against the majority of existing BCCs in these patients (10).…”
Section: Discussionmentioning
confidence: 77%